An importance measure of a CNC lathe considering failure correlations. (6th August 2021) - Gu, Dongwei; Zhong, Yuhong; Xu, Zhen; Chen, Bingkun; Wang, Zhiqiong
Abstract: Failure correlation is a physical phenomenon observed, for example, in CNC (computer numerical control) lathe applications. Reliability importance measure considering failure correlation is an effective measure to identify the importance of CNC lathe. This paper fully considers the failure correlation among the subsystems of the CNC lathe. Based on the Copula function, the joint reliability model of each subsystem of the CNC lathe is established. Three methods ( D ‐test, the average cumulative error, and the root mean square error) are used to compare the joint reliability models under different Copula functions. Then ascertained the Clayton Copula model can describe the failure correlation reliability of CNC lathe most accurately. The reliability dynamic importance measure can judge the difference in CNC lathe subsystem importance measure more accurately. In this paper, the reliability dynamic core importance measure is proposed to analyze the potential of the CNC lathe subsystems for improvement. It can determine that the servo subsystem is the crucial part of the CNC lathe for priority improvement.